Tracing the Footsteps of Alcohol: The Impact of Legal-Illegal Consumption and Distribution on Health and Society Viewed from Anomie Theory - Nurhadiyanto, Lucky; Rozak, Abdur; Anorawi, Rafi (Journal of Social Interactions and Humanities, 2024)
This research aims to analyze the impact of alcohol consumption and legal-illegal distribution of alcohol on the health and social aspects of society. This research uses observation data, case studies and interviews. This research uses a qualitative descriptive approach which uses empirical research. By viewing Merton's concept of anomie from the perspective of alcohol consumption, we can see how individuals and society respond to cultural pressures, social norms, and laws related to alcohol, as well as their impact on overall health and social dynamics. The policy implications found from this research can provide a basis for developing more effective intervention strategies in improving public health and welfare related to alcohol consumption and legal-illegal distribution. It is hoped that this research will contribute to further understanding of the complex dynamics between alcohol consumption, regulation, and its impact on health and society.